The Meaning of Marriage for Single Career Women in Urban Areas - Puspitaningrum, Patricia Angelin Elfina; Philia, Mary (Universitas Syiah Kuala, 2025)
This study explores the meaning of marriage among single career women living in urban areas, focusing on how they interpret marriage in relation to ambition, gender roles, and happiness. Using a qualitative phenomenological approach with Interpretative Phenomenological Analysis (IPA), the research involved an in-depth interview with a 30-year-old female military doctor. Thematic analysis revealed three main themes: (1) Balancing Ambition and Love, where the participant viewed ambition and affection as two essential but often conflicting life forces; (2) Gender Roles in Marriage, where she expressed egalitarian views, emphasizing equal sharing of domestic and financial responsibilities; and (3) Marriage and Happiness, where communication, emotional maturity, and mutual respect were seen as foundations of marital harmony. For the participant, marriage is not an obligation but a partnership rooted in trust, empathy, and shared goals. She believes happiness in marriage depends on openness and understanding rather than social conformity or material success. Her perspective reflects a modern, independent woman navigating between traditional expectations and personal self-fulfillment. The findings highlight how single career women reinterpret marriage as a personal choice grounded in equality and self-awareness, offering valuable insights for developmental and social psychology, especially regarding the impact of cultural norms and gender roles on womens life decisions.